Active feeding of downstream migrating juvenile pink salmon (Oncorhynchus gorbuscha) revealed in a large Barents Sea river using diet and stable isotope analysis - Erkinaro, Jaakko; Orell, Panu; Kytökorpi, Mikko; Pohjola, Jan-Peter; Power, Michael (Journal of Fish Biology)
2023